(untitled) (Revista científica Olimpia, 2019)
This book is part of the result of a PhD thesis in Physical Culture Sciences whose result is being applied in several provinces of Cuba and in many special schools of Venezuela where these people with disabilities are present, within its content is a methodology Through which the Physical Education teacher is oriented to adapt the physical activities for this group specifically, as well as the dosage of activities oriented by levels and the physical activities to develop to achieve a correct process of teaching learning the physical abilities and abilities Basic motor skills with the aim of preparing these children for their future adult and independent life.